Advancing NR-V2X: Evaluating Mode 2 Performance Through Analytical Modeling and Simulations - Mahmoud Elsharief; Saifur Rahman Sabuj; Nathan Jeong; Han-Shin Jo (IEEE Access)
The third-generation partnership project (3GPP) has introduced a new radio (NR) for vehicle-to-everything (V2X). It assigns Mode 2 to allow user equipment (UEs) to reserve and select radio resources autonomously. This paper comprehensively analyzes the NR-V2X Mode 2 performance, focusing on the packet reception ratio (PRR). PRR is a critical metric in evaluating the efficacy of vehicular networks. We propose an analytical model that correlates PRR with the distance between the transmitter and receiver. This model helps us understand NR-V2X Mode 2 communication in autonomous operation. We also conduct simulations to validate our model. These simulations reflect various vehicular traffic scenarios. Our findings reveal strategies to optimize resource allocation in NR-V2X Mode 2 networks. Specifically, altering specific parameters can notably enhance network performance. This research is valuable for both academic and industry circles. It provides insights into improving communications in autonomous vehicles. Moreover, it offers practical guidance for industry experts aiming to advance V2X communication in the era of autonomous driving.